Tunneled antibiotic-impregnated vs. bolt-connected, non-coated external ventricular drainage: a comparison of complications - Ortega-Angulo, Celia; Royuela, Ana; Kalantari, Teresa; Rodríguez-Boto, Gregorio; Gutierrez-Gonzalez, Raquel (Frontiers in Neurology, 2023)
Background External ventricular drainage (EVD) is a common emergency neurosurgical procedure, but it is not free of adverse events. The aim of this study is to compare the complication rate of two frequently used EVD types, namely, tunneled antibiotic-impregnated catheters (Bactiseal©) and bolt-connected non-coated devices (Camino©). Methods All EVDs placed between 1 March 2015 and 31 December 2017 were registered. Procedures performed with any catheter different from Bactiseal© or Camino© EVD with incomplete follow-up and those EVDs placed due to infectious disease were excluded. Demographic and clinical variables, as well as the overall complication rate (infection, hemorrhage, obstruction, malposition of the catheter, and involuntary pull-out of the device) and the need for replacement of the EVD, were collected. Results A total of 77 EVDs were finally considered for analysis (40 Bactiseal® and 37 Camino®). There was a statistically significant difference in diagnosis and also in the location of the procedure, as more bolt-connected EVD was placed outside the operating room (97.3 vs. 23.5%, p < 0.001) due to emergent pathologies such as vascular diseases and spontaneous hemorrhages. In the univariate analysis, a statistically significantly higher rate of catheter involuntary pull-out (29.7 vs. 7.5%, p = 0.012) and the need for EVD replacement (32.4 vs. 12.5%, p = 0.035) was found in the Camino cohort. However, those differences could not be confirmed with multivariable analysis, which showed no association between the type of catheter and any of the studied complications. Ventriculostomy duration was identified as a risk factor for infection (OR 1.09, 95% CI 1.02–1.18). Conclusion No significant differences were observed regarding infection, hemorrhage, obstruction, malposition, involuntary catheter pull-out, and the need for EVD replacement when comparing non-impregnated bolt-connected EVDs (Camino®) with tunneled antibiotic-impregnated catheters (Bactiseal®). The duration of EVD was associated with an increased risk of infection.